Electrospun ZnO–SnO2 Composite Nanofibers and Enhanced Sensing Properties to SF6 Decomposition Byproduct H2S - Lu, Zhaorui; Zhou, Qu; Wang, Caisheng; Wei, Zhijie; Xu, Lingna; Gui, Yingang (Frontiers in Chemistry, 2018)
Hydrogen sulfide (H2S) is an important decomposition component of sulfur hexafluoride (SF6), which has been extensively used in gas-insulated switchgear (GIS) power equipments for insulating and arc-quenching medium. In this work, H2S gas sensor based on electrospun ZnO-SnO2 composite nanofibers was fabricated. The structure and morphology of the electrospun ZnO-SnO2 nanofibers were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray spectrometers (EDS), X-ray photoelectron spectroscopy (XPS) and Brunauer–Emmett–Teller (BET), respectively. Side heat sensors were fabricated with the electrospun ZnO-SnO2 nanofibers and the gas sensing behaviors to H2S were systematically investigated. The proposed ZnO–SnO2 composite nanofibers sensor demonstrated lower optimum operating temperature, enhanced sensing response, quick response/recovery time and good long-term stability against H2S. The measured optimum operating temperature of the ZnO–SnO2 nanofibers sensor to 50 ppm H2S gas was about 250℃ with a response of 66.23, which was 6 times larger than pure SnO2 nanofibers sensor. The detection limit of the fabricated ZnO–SnO2 nanofibers sensor towards H2S gas can be as low as 0.5 ppm, and the response and recovery times were 18 s and 32 s, respectively. Finally, a plausible sensing mechanism for the proposed ZnO–SnO2 composite nanofibers sensor to H2S was also discussed.